Rosset Enterprise / Amilia Abdul Majid... [et al.] - Abdul Majid, Amilia; Mustafa, Khairuliza Azlina; Mohd Nasir, Nazliza; Bajuri, Noor Adnie; Che Daud, Noor Azida (2000)
Rosset Enterprise is a partnership company which runs fruit juices manufacturing in Penang. They started their business in 1 January 2002.